Analysis of Work Motivation in Increasing the Productivity of RRI Medan Employee Performance - Miranda, Miranda; Syarvina, Wahyu (Universitas Ibn Khaldun, 2024)
This research aims to determine the motivation used to increase employee productivity at LPP RRI Medan and the efforts made by organizations or companies to motivate their employees. The research results show that LPP RRI Medan provides motivation to its employees in two ways, namely materially and non-materially, but when implemented, it is inconsistent in providing work motivation to its employees. This incident resulted in many employees who were not motivated to do their jobs well. Efforts taken include not being too harsh in criticizing and correcting employees, for example, when an employee makes a mistake, the head of the company should reprimand them properly and direct the employee to make improvements. Then often carry out controls during working hours so that employees feel cared for and they feel motivated by the presence of the head of the company or organization. This study uses a qualitative method. Research is carried out directly in the field or object where all data is collected by observation and interviews.